(untitled) (مجلة إحالات, 2026)
"Islamic literature" is a term of value. Literature or morals of its various races form an important part of the anthropology and heritage of man, Islam as an enriched cultural religion and has influenced many human morals and cultures that cannot objectively be hostile or rejected. This term is part of the global classifications of ethics that carry legacies and ideology. We concluded that there was no reason to reject the term "Islamic literature", because there was no contradiction with man’s humanity and the universality of literature in all the connotations to which the word Islam referred us, and the foundations and milestones defined by its owners, while seeking excuse for those who reject it, so that it was not crammed into the corner and bombarded with all the outrageous connotations.